Examining the Link Between Intolerance of Uncertainty and Positive and Negative Urgency in Veterans With Comorbid Posttraumatic Stress Disorder and Substance Use Disorders. Issue 1 (January 2021) - McGuire, Adam P.; Hayden, Candice L.; Zambrano-Vazquez, Laura; Connolly, Kevin M.
Abstract : Abstract: Posttraumatic stress disorder (PTSD) and substance use disorders (SUD) are highly comorbid among the veteran population. Impulsivity, particularly negative and positive urgency, are prevalent within this dual-diagnosis population and associated with negative outcomes. One possible correlate of negative/positive urgency is intolerance of uncertainty (IU). IU is associated with exacerbated PTSD symptom severity and increased risk for substance use. However, few studies have examined the link between IU and negative/positive urgency in dual-diagnosis populations. This study aimed to examine whether there was a significant association between trait IU and baseline negative and positive urgency in veterans seeking treatment for both PTSD and SUD. In a sample of 114 veterans from a 6-week residential treatment program, IU was significantly associated with higher negative and positive urgency. Further research is warranted to extend these findings and examine whether IU plays an important role in negative/positive urgency for dual-diagnosis populations.